Analytical solution for nonlinear consolidation of combined electroosmosis-vacuum-surcharge preloading. (May 2020) - Wang, Liujiang; Huang, Penghua; Liu, Sihong; Alonso, Eduardo
Abstract: In this study, analytical solutions of the consolidation of vertical drains combined with electroosmosis-vacuum-surcharge preloading are derived considering void ratio-dependent compressibility, hydraulic permeability and permeability of electroosmosis. In addition, radial and vertical flow, changes of the hydraulic and electroosmosis permeabilities in the smear zone, and time‐dependent surcharge preloading are also considered. The solution is verified by comparing it with experimental result and numerical solution in the previous literature. Finally, a parametric study is conducted to investigate the influence of considering nonlinearity, smear zone, and non-synchronous change of hydraulic and electroosmosis permeability in void ratio. The result indicates that the average negative pore water pressure under combined electroosmosis-vacuum-surcharge preloading is larger with the consideration of nonlinear change of the soil parameters, and the consolidation rate is also faster. The presence of a smear zone decreases the consolidation rate and increases the final settlement. A slower consolidation rate is obtained for the smear zone with the large radius and the less permeable. The consolidation rate, final settlement and negative pore water pressure increase for the soils with the large value of electroosmosis permeability index. In addition, the decrease of the vertical hydraulic permeability will increase the final settlement and consolidation time.